2004
DOI: 10.1096/fj.03-0847fje
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields increase in vitro and in vivo angiogenesis through endothelial release of FGF‐2

Abstract: Pulsed electromagnetic fields (PEMF) have been shown to be clinically beneficial, but their mechanism of action remains unclear. The present study examined the impact of PEMF on angiogenesis, a process critical for successful healing of various tissues. PEMF increased the degree of endothelial cell tubulization (sevenfold) and proliferation (threefold) in vitro. Media from PEMF cultures had a similar stimulatory effect, but heat denaturation ablated this activity. In addition, conditioned media was able to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(152 citation statements)
references
References 21 publications
(19 reference statements)
5
140
0
Order By: Relevance
“…Most investigations on the mechanism of action of IC technology have been performed with the PEMF signal which is FDA approved for fracture healing but not spinal fusion [1,4,8,11,29,43,44,51,64]. There is only one study using the PEMF signal that is clinically approved for spinal fusions [61] and a few studies with CMF [11,20,21,58].…”
Section: Inductive Couplingmentioning
confidence: 99%
“…Most investigations on the mechanism of action of IC technology have been performed with the PEMF signal which is FDA approved for fracture healing but not spinal fusion [1,4,8,11,29,43,44,51,64]. There is only one study using the PEMF signal that is clinically approved for spinal fusions [61] and a few studies with CMF [11,20,21,58].…”
Section: Inductive Couplingmentioning
confidence: 99%
“…However, SMF did not induce any significant changes in the VEGF-A-increased number of bifurcations in any part of the wells [25]. Additionally it is reported that Pulsed electromagnetic fields (PEMF) had ability to increase in vitro and in vivo angiogenesis through endothelial release of FGF-2 and inducing paracrine and autocrine changes in the surrounding tissues [26]. In 2001 Williams reported that exposure to therapeutic electromagnetic fields (10 minutes per day with 0.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported acceleration of angiogenesis within 1 week of commencing electromagnetic therapy [27]. Another study reported ischemia in the bone occurs within 5 to 6 days after corticosteroid administration [10].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, prevention of bone ischemia might also prevent steroid-induced ON. We considered pulsed electromagnetic field stimulation could be a preventive therapy because it promotes angiogenesis [11,19,27] and dilates blood vessels [23]. We speculated it might also influence the enlargement of intramedullary fat cells since that is reportedly a potential mechanism in bone necrosis [14,15,28].…”
Section: Introductionmentioning
confidence: 99%